Municipal Representatives’ Accounts of Decision-Making Practices during Geriatric Case Conferences - Nielsen, Søren Beck (HERMES - Journal of Language and Communication in Business, 2010)
This article addresses questions of elucidation in talk-in-interaction. How do social actors give accounts of what they are doing? To what degree do actors sustain a taken-for-granted level of reasoning? The analysis is based upon naturally occurring data consisting of a corpus of audio recorded case conferences at various geriatric wards in Danish hospitals. The article elaborates one of the important insights of Harold Garﬁnkel regarding the relationship between discourse and social interaction: as a general characteristic, people tend to treat their fellow interlocutors’ conversational contributions as adequate for-all-practical-purposes. Speciﬁcally, the article investigates how Danish municipal representatives account for their decisions about whether or not senior citizens are to be referred to residential homes. This practice, I demonstrate, is characterized by non-explicitness with regards to rules and regulations. Instead, municipal representatives make use of developmental discourse: a worsened condition is used to justify a referral to a residential home. On the other hand, an improved condition is used to justify that an elderly citizen is not referred to a residential home.